Rhodium-catalyzed P–P bond exchange reaction of diphosphine disulfides. Issue 93 (2nd November 2016) - Arisawa, Mieko; Yamada, Tomoki; Tanii, Saori; Kawada, Yuta; Hashimoto, Hisako; Yamaguchi, Masahiko
Abstract : A rhodium-catalyzed exchange reaction of diphosphine disulfides, a diphosphine oxide, and a diphosphine is developed. Various symmetric diphosphine disulfides containing alkyl and phenyl groups are exchanged. Abstract : A rhodium-catalyzed exchange reaction of diphosphine disulfides, a diphosphine oxide, and a diphosphine is developed. Various symmetric diphosphine disulfides containing alkyl and phenyl groups are exchanged, giving equilibrium mixtures, from which unsymmetric diphosphine disulfides are readily separated by silica gel chromatography. The resulting unsymmetric diphosphine disulfide is regioselectively added to an aldehyde.